The linguistic characteristics of the language of human rights and its use in reality as the kingdom of God in the light of Speech Act Theory - Cho, Anna (HTS teologiese studies, 2019)
Human rights, a language that keeps public order, is realised in ordinary life by language characteristics according to social rules. Despite this fact, research that considers the linguistic features of human rights relating to its use and effects in terms of the kingdom of God in the present world seems to have not been attempted or seldom attempted. Thus, this article proposes to examine the language of human rights by means of Speech Act Theory. The approach is predicated upon the language use as performative acts. The approach shows the language of human rights with performative language by seeking to uncover the operation and effects of language of rights in real-life situations. The thrust of this article implies how we can explain the semantics of human rights and execute them in ordinary life in terms of God’s kingdom.